Melasma in pregnancy: causes and treatment (Research, Society and Development, 2022)
The present research deals with Melasma in pregnancy and aims to talk about its causes and treatment. Thus, the objective of this work is to discuss the main prevention factors and existing treatments for Melasma in pregnancy. Therefore, the secondary objectives are to conceptualize Melasma, present the causes of the emergence of Melasma and its development factors and relate the emergence of Melasma to pregnancy. The method used in the literature review methodology is integrative and qualitative research, books and articles published from 2012-2022, that is, up to 10 years ago. Scientific studies were searched in the following databases: MedLine, Lilacs, Scielo, using the words: Melasma, pregnancy, causes, treatment. In the final considerations, the importance of prevention is indicated, in particular, through less exposure to sunlight and treatments that are not aggressive during pregnancy and lactation, through bleaching, especially vitamin C.